3D Nanoprinting of All-Metal Nanoprobes for Electric AFM Modes - Lukas Matthias Seewald; Jürgen Sattelkow; Michele Brugger-Hatzl; Gerald Kothleitner; Hajo Frerichs; Christian Schwalb; Stefan Hummel; Harald Plank (Nanomaterials, 2022)
3D nanoprinting via focused electron beam induced deposition (FEBID) is applied for fabrication of all-metal nanoprobes for atomic force microscopy (AFM)-based electrical operation modes. The 3D tip concept is based on a hollow-cone (HC) design, with all-metal material properties and apex radii in the sub-10 nm regime to allow for high-resolution imaging during morphological imaging, conductive AFM (CAFM) and electrostatic force microscopy (EFM). The study starts with design aspects to motivate the proposed HC architecture, followed by detailed fabrication characterization to identify and optimize FEBID process parameters. To arrive at desired material properties, e-beam assisted purification in low-pressure water atmospheres was applied at room temperature, which enabled the removal of carbon impurities from as-deposited structures. The microstructure of final HCs was analyzed via scanning transmission electron microscopy—high-angle annular dark field (STEM-HAADF), whereas electrical and mechanical properties were investigated in situ using micromanipulators. Finally, AFM/EFM/CAFM measurements were performed in comparison to non-functional, high-resolution tips and commercially available electric probes. In essence, we demonstrate that the proposed all-metal HCs provide the resolution capabilities of the former, with the electric conductivity of the latter onboard, combining both assets in one design.